THE EFFECT OF TAX AVOIDANCE, TAX RISK, AND PROFITABILITY ON THE COST OF DEBT IN ENERGY SECTOR COMPANIES LISTED ON THE IDX FOR THE 2019-2021 PERIOD - P’briel Stevant Adi Saragih; Harlyn Siagian (Sean Institute, 2023)
As for the main direction of this research is to be able to understand the relationship of tax avoidancetax risk and profitability to the variable cost of debt. As information material to meet research needs, data is used through the financial reports ofenergy sector companies listed on the IDX for the periode 2019-2021. The population of this study is 74 companies, this population is taken from companies operating in the energy sector which are listed on the IDX. The author took 20 companies as areference sample in this study. In the results it was found that tax avoidance did not affect the cost of debt and tax risk had no effect nor was it significant on cost of debt and tax avoidance, tax risk and profitability proved to have no effect significant for energy sector companies listed on the IDX for the 2019-2021 period.